Sensing grain and seed moisture and density from dielectric properties - Nelson, Stuart O.; Trabelsi, D. Sc. Samir (International Journal of Agricultural and Biological Engineering, 2011)
Abstract: The importance of moisture measurement in grain and seed is discussed, and a brief history of the development of moisture sensing instruments, based on sensing of dielectric properties of these materials, is presented. Data are presented graphically on the permittivities or dielectric properties of grain and seed showing their variation with frequency, moisture content, temperature, and bulk density, and references are cited for further information. More recent developments on microwave measurements for moisture content and bulk density sensing are briefly described, and numerous studies are cited providing sources of information on these newer techniques. Keywords: sensing, dielectric properties, moisture content, density, permittivity, cereal grain, oilseed DOI: 10.3965/j.issn.1934-6344.2011.01.075-081 Citation: Stuart O. Nelson, D. Sc. Samir Trabelsi. Sensing grain and seed moisture and density from dielectric properties. Int J Agric & Biol Eng, 2011; 4(1): 75<span style="font-size: 9pt; line-height: 130%; font-family: